Measuring the Effect of Restructuring on Corporate Performance: The Case of Management Buyouts - Smart, Scott B.; Waldfogel, Joel (The Review of Economics and Statistics, 1994)
Scott B. Smart, Joel Waldfogel, Measuring the Effect of Restructuring on Corporate Performance: The Case of Management Buyouts, The Review of Economics and Statistics, Vol. 76, No. 3 (Aug., 1994), pp. 503-511